1991
DOI: 10.1128/aem.57.7.2057-2062.1991
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Thiobacillus ferrooxidans on Formic Acid

Abstract: A variety of acidophilic microorganisms were shown to be capable of oxidizing formate. These included Thiobacillusferrooxidans ATCC 21834, which, however, could not grow on formate in normal batch cultures. However, the organism could be grown on formate when the substrate supply was growth limiting, e.g., in formate-limited chemostat cultures. The cell densities achieved by the use of the latter cultivation method were higher than cell densities reported for growth of T. ferrooxidans on ferrous iron or reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…In contrast, aerobic growth yields of T. ferrooxidans on inorganic sulfur compounds are over twofold higher than the growth yield on ferrous iron (5). The cell yields observed in the present study are consistent with a model proposed previously (13) in which the ferric ironreducing enzyme system accepts electrons at the redox level of the ferrous iron oxidoreductase. However, more information about cell size and biomass composition is required before definitive conclusions can be drawn on the energetic efficiency of anaerobic growth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, aerobic growth yields of T. ferrooxidans on inorganic sulfur compounds are over twofold higher than the growth yield on ferrous iron (5). The cell yields observed in the present study are consistent with a model proposed previously (13) in which the ferric ironreducing enzyme system accepts electrons at the redox level of the ferrous iron oxidoreductase. However, more information about cell size and biomass composition is required before definitive conclusions can be drawn on the energetic efficiency of anaerobic growth.…”
Section: Discussionsupporting
confidence: 92%
“…Thiobacillus ferrooxidans is an obligately autotrophic, acidophilic bacterium. Autotrophic growth can be supported by the oxidation of a variety of inorganic sulfur compounds, ferrous iron (6,8), molecular hydrogen (4), or formic acid (13). T. ferrooxidans and physiologically related bacteria are of great economical importance because of their involvement in the biological leaching of copper and uranium ores and the biooxidation of gold ores (16).…”
mentioning
confidence: 99%
“…Most iron-and sulfur-oxidising acidophiles are regarded as autotrophic, though the ability to assimilate organic carbon has been demonstrated with some of these (e.g. utilisation of formic acid by T. ferrooxidans [11]). Other prokaryotes which catalyse the dissimilatory oxidation of iron and/or RSCs are either mixotrophic (i.e.…”
Section: Autotrophic and Heterotrophic Life-stylesmentioning
confidence: 99%
“…Two species of mesophilic acidophilic bacteria, Thiobacillus ferrooxidans and Leptospirillum ferrooxidans, have been implicated as being the most significant microorganisms involved in sulfide mineral oxidation, although moderately thermophilic (or thermotolerant) bacteria and extremely thermophilic archaea are also known to be important in certain situations, such as self-heating coal spoils and bioleaching operations in which temperatures exceed 40°C. Both T. ferrooxidans and L. ferrooxidans are generally regarded as obligate chemolithotrophs and synthesize cell carbon via enzymic fixation of CO 2 , although it has been shown that T. ferrooxidans has a limited capacity to utilize organic carbon (22). Two mechanisms ("direct" and "indirect") have been described as the mechanisms by which metal-mobilizing acidophilic bacteria degrade sulfide minerals, although electrochemical interactions which occur between minerals during bacterial leaching are also thought to be important in accelerating mineral dissolution (20).…”
mentioning
confidence: 99%